2015
DOI: 10.1371/journal.pone.0135512
|View full text |Cite
|
Sign up to set email alerts
|

HLA Allele E*01:01 Is Associated with a Reduced Risk of EBV-Related Classical Hodgkin Lymphoma Independently of HLA-A*01/*02

Abstract: BackgroundAn inefficient immune response against Epstein-Barr virus (EBV) infection is related to the pathogenesis of a subgroup of classical Hodgkin lymphomas (cHL). Some EBV immune-evasion mechanisms target HLA presentation, including the non-classical HLA-E molecule. HLA-E can be recognized by T cells via the TCR, and it also regulates natural killer (NK) cell signaling through the inhibitory CD94/NKG2A receptor. Some evidences indicate that EBV-infected B-cells promote the proliferation of NK subsets beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…These results have been supported by another work [75]. At last, genotypes with at least one copy of HLA-E R are associated with lower risk of EBV-related classical Hodgkin’s lymphoma [76].…”
Section: Hla-e Dimorphism and Cancersupporting
confidence: 64%
“…These results have been supported by another work [75]. At last, genotypes with at least one copy of HLA-E R are associated with lower risk of EBV-related classical Hodgkin’s lymphoma [76].…”
Section: Hla-e Dimorphism and Cancersupporting
confidence: 64%
“…Interestingly, a recently published study identified the HLA-E*0101 variant as a protective factor for EBV-related classic Hodgkin lymphoma. 30 This not only supports our findings but also suggests that the LMP-1 peptide-mediated upregulation of HLA-E may play a role in EBV-associated lymphoproliferative diseases in general. In combination with our data, this highlights the need for further assessment of the potential of LMP-1 variant and HLA-E analysis to identify patients generally at risk for EBV-associated lymphoproliferative diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies reported a higher prevalence of the HLA-E*01:03 allele or the HLA-E*01:03/01:03 genotype in infectious diseases [ 38 ] and several cancer types including nasopharyngeal carcinoma, serous ovarian cancer, and acute leukemia [ 9 , 39 , 40 ]. Interestingly, the HLA-E*01:01 allele seems to be underrepresented in classical Hodgkin lymphomas, especially among Epstein Barr virus (EBV)-positive cases compared to healthy controls [ 41 ]. We observed a slightly higher prevalence of the HLA-E*01:01 genotype in aggressive B-NHL.…”
Section: Discussionmentioning
confidence: 99%